BIOMIMETIC SYNTHESIS AND ANTIBACTERIAL PROPERTIES OF STRONTIUM OXIDE NANOPARTICLES USING OCIMUM SANCTUM LEAF EXTRACT - G, Apsana; Pp, George; N, Devanna; R, Yuvasravana (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The investigation and synthesis of nanoparticles using green chemical methods is an emerging field due to ecologically derived materials. In the present study, the reaction under microwave irradiation technique is proposed for synthesizing the strontium oxide nanoparticles (SrO NPs) by reacting the strontium nitrate powder with Ocimum sanctum L. leaf extract followed by heat treatment at 500oC for 2 h. Methods: The crystalline nature, size, and morphological structure of the SrO powder sample were characterized by techniques such as powder X-ray diffraction (PXRD), scanning electron microscopy, ultraviolet (UV)-Vis spectroscopy, Fourier-transform infrared spectroscopy (FTIR) and photoluminescence (PL) spectral analysis. To investigate the antibacterial properties of SrO NPs, pathogens such as Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Proteus vulgaris, Klebsiella pneumonia, and Morganella morganii was tested in Mueller–Hinton disc diffusion method. Results: The particle size of the SrO NPs is calculated to be 42 nm using Debye–Scherrer equation. The SrO NPs exhibited absorption peak in the range of 250–350 nm centered at 274 nm in UV region. In addition, it is demonstrated that band gap energy was calculated to be 5.39 eV from Tauc's plot. The SrO NPs has shown the efficient antibacterial effect by inhibiting zone against Gram-negative bacteria. Conclusion: The main aim of the study is to synthesize cost-effective and eco-friendly green synthesis of SrO NPs from the OS (O. sanctum) leaf extract and their characterization. The mechanism for the formation of SrO NPs in the presence of eugenol as reducing agent is also discussed. The present green chemical approach using plant-based materials for the synthesis of nanoparticles enhances the eco-friendliness, compatibility, effectiveness, and reduces the toxicity.